Microwave assisted extraction of essential oil and pectin from orange peel in different stages of maturity. - Durán Barón, R.; Villa, A. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2014)
Â The effect of solvent (water), power, time of microwave exposure and maturity stage of the orange fruit on the essential oil extraction yield and its chemical characteristics and on the pectin extraction yield from Valencia orange peels was studied. The extraction of essential oil by microwave and subsequent extraction of pectin with conventional heating was carried out from the epicarp of oranges sampled from 16 trees in lots of one hectare. The essential oil extraction yield was slightly higher using additional water under the best extraction conditions (600 W, 10 min), and the limonene content, determined by GC- MS, was between 90.5 and 97.9%. Scanning Electron Microscopy analyses after of essential oil extraction showed that the intracellular spaces of the plant tissue increased with time under microwave irradiation. Without solvent, the orange peel was carbonized when the microwave power was higher than 600 W. After essential oil extraction, the highest pectin extraction yield was obtained with the orange peel treated with water. The content of essential oil decreased with the maturity (0.14 a 0.08%). The content of limonene did not depend on the maturity stage. The Î²-mirceno, sabinene, felandrene y carene decreased with maturity, opposite happened with the Î±-pinene. The highest pectin extraction yield (7.5%) was obtained with orange peels in maturity stage two.